2019
DOI: 10.2355/isijinternational.isijint-2019-069
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Effect on the Nitrogen Super-Saturation Process into AISI316 at 623 K

Abstract: Coarse and fine grained AISI316 substrates were prepared to describe the grain size effect on the inner nitriding behavior at 623 K by using the high density plasma nitriding without precipitation of nitrides. In case of coarse grained AISI316, the nitriding process advanced homogeneously in one part of nitrided layer with high nitrogen content, and, heterogeneously in its other part. In the former, γ-α ' two-phase, fine microstructure was uniformly formed by the phase transformation and plastic straining with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The γ N -α N two-phase nanostructure comes back to a nearly single γ N -phase in Figure 6c. As reported in [14,15,19], the nitrogen solute diffuses through the refined grain and zone boundaries in the nitrogen supersaturation. This microstructure change is caused by the autonomous mode change from heterogeneous nitrogen supersaturation to homogeneous nitrogen supersaturation.…”
Section: Microstructure Of Ngss304 and Fgss304 Plates After Plasma Nitriding At 623 K For 144 Ksmentioning
confidence: 67%
See 3 more Smart Citations
“…The γ N -α N two-phase nanostructure comes back to a nearly single γ N -phase in Figure 6c. As reported in [14,15,19], the nitrogen solute diffuses through the refined grain and zone boundaries in the nitrogen supersaturation. This microstructure change is caused by the autonomous mode change from heterogeneous nitrogen supersaturation to homogeneous nitrogen supersaturation.…”
Section: Microstructure Of Ngss304 and Fgss304 Plates After Plasma Nitriding At 623 K For 144 Ksmentioning
confidence: 67%
“…This non-zero nitrogen content beyond the nitriding front end implies that the nitrogen supersaturation advances heterogeneously even below the nitrided layer. EBSD was a powerful tool to describe the microstructure evolution during plasma nitriding as stated in [9,[12][13][14][15]. Figure 6a depicts the IPF distribution from the surface to the depth (d) of 130 µm.…”
Section: Microstructure Of Ngss304 and Fgss304 Plates After Plasma Nitriding At 623 K For 144 Ksmentioning
confidence: 99%
See 2 more Smart Citations
“…As had been discussed in [29,30], the initial grain size of AISI316 has influence on the inner nitriding behavior; homogeneity in nitriding process is enhanced with reduction of initial grain size. This finding suggested that fine-grained AISI316 or FGSS316 structural components and parts could be homogeneously nitrided on the surface with a little effect of heterogeneous nitriding on the microstructure below NFE.…”
Section: Microstructure Evolution In Fgss316 Wiresmentioning
confidence: 99%